2015
DOI: 10.1037/cns0000073
|View full text |Cite
|
Sign up to set email alerts
|

Sense of agency: Theory, methods, and application.

Abstract: Sense of agency is an area of growing research interest with important implications for our understanding of consciousness; motor control; psychiatric symptoms, such as passivity phenomena; hypnosis; and the neuropsychological basis of moral and legal responsibility. These seemingly disparate research topics all overlap in a push toward increasingly specific models of the subjective phenomenology of action. In December 2013, a group of cognitive scientists, philosophers, and clinicians working on sense of agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…We used multiple measures including an embodiment scale commonly used in RHI studies (Longo et al, 2008b); the Sense of Agency Rating Scale (SOARS), which has previously been used to assess alterations to feelings of agency in studies of self-generated actions in hypnotic and clinical contexts (Polito et al, 2013, 2014, 2015); and rating scale items for presence typically used in studies of VR experiences (Sanchez-Vives and Slater, 2005). We found multivariate effects of FORM, TOUCH, and OFFSET across all measures, confirming that each of these cues has a broad influence on self-representation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used multiple measures including an embodiment scale commonly used in RHI studies (Longo et al, 2008b); the Sense of Agency Rating Scale (SOARS), which has previously been used to assess alterations to feelings of agency in studies of self-generated actions in hypnotic and clinical contexts (Polito et al, 2013, 2014, 2015); and rating scale items for presence typically used in studies of VR experiences (Sanchez-Vives and Slater, 2005). We found multivariate effects of FORM, TOUCH, and OFFSET across all measures, confirming that each of these cues has a broad influence on self-representation.…”
Section: Discussionmentioning
confidence: 99%
“…In another line of research, hypnotic suggestions have been shown to induce significant changes in the way that susceptible participants generate and monitor actions, leading to marked alterations to the sense of agency (Polito et al, 2014). Sense of agency has been measured in a variety of ways including explicit ratings of first-person experience (Bowers, 1981; Polito et al, 2014, 2015) and indirect, implicit measures such as intentional binding, which uses participants' time judgments regarding causal actions in a behavioral task as a proxy for agency (Haggard et al, 2002). …”
Section: Introductionmentioning
confidence: 99%